Antioxidant activity of extracts from the aril of Torreya fargesii Franch. And its protection on the oxidation of DHA algal oil. Issue 1 (1st January 2018) - Zhou, Xianrong; Shang, Jin; Wang, Jianhua; Jiang, Bo; Wang, Qing
ABSTRACT: The hydrosoluble extract from a processing waste, aril of Torreya fargesii Franch. ( abbr .as Torreya F), was investigated for its antioxidative properties and resulting protective effect on the oxidation of DHA (docosahexaenoic acid) algal oil. The aril extract of Torreya F contained about 125.2 mg GAE/g dry extract total polyphenols and 18.5 mg RT/g dry extract total flavonoids. The scavenging ability on the DPPH (1, 1-diphenyl −2-picrylhydrazyl), hydroxyl and superoxide anion radicals of aril extract of Torreya F was stronger than that of commercial ascorbyl palmitate. With the addition of Torreya F aril extract, the increasing peroxide value and acid value of DHA algal oil was inhibited both in the long-term storage test and the accelerating Schaal test.